Percorsi di salute e maternità fra immigrate filippine e ucraine. Reti, possibilità e barriere - Milena Greco (EtnoAntropologia, 2019)
This article intends to provide, considering critical medical anthropology, a deeper insight on the opportunities and dynamics of accessing health services when reproductive health is concerned and on childbirth, seen as a “bio-social event”, by Filipino and Ukrainian female migrants, living in two different areas of Italy. Starting by narrating their stories, it will be described how, despite protection, these women must still face many issues and barriers, as their path is often transnational.